The influence of wearing schemes and supportive telephone calls on adherence in accelerometry measurement: results of a randomized controlled trial - van den Berg, Neeltje (Patient Prefer Adherence, 2017)
BACKGROUND: Physical activity (PA) can be assessed by accelerometer monitors. However, a high adherence to wearing this device is essential to obtain valid data. In this study, the influence of different wearing schemes and additional supportive phone calls (SPCs) on adherence was examined. METHODS: A randomized study with four groups was conducted in the context of a health examination program among participants aged 40–75 years without a history of cardiovascular diseases. Participants were recruited in different settings (general medical practices, job center, and health insurance). The participants were asked to wear an accelerometer for 7 consecutive days according to the wearing scheme “day and night” or “day only” and received or did not receive SPCs. Full adherence was defined as a total wearing time of 98 hours (between 8 am and 10 pm during 7 days). A generalized linear model was used to calculate the difference between the maximum possible and the observed adherence. RESULTS: Adherence could be assessed for 249 participants (mean age: 56.40 years; standard deviation [SD] 9.83, 40% males). The mean wearing time was 84.04 hours (SD 20.75). Participants with the wearing scheme day and night were significantly more adherent than participants with the wearing scheme day only (incidence rate ratio [IRR] 0.63; P=0.005). SPCs had no additional effect on adherence (IRR 0.80; P=0.168). CONCLUSION: To assess PA, the wearing scheme day and night provides the best possible adherence in this group of participants. Further studies are necessary to examine adherence and the effects of additional SPCs in other samples or settings.